Interpretation of Word Meanings in the Uzbek Language Corpus - Fozilova Firuza (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article analyzes the issues of interpreting word meanings in the Uzbek language corpus. The theoretical foundations of corpus linguistics, specific features of semantic description, and principles of identifying word meanings based on context are discussed. During the research, the scientific and practical significance of revealing the semantic characteristics of lexical units in the Uzbek language corpus was highlighted. Furthermore, the role of corpus materials in the development of electronic dictionaries, machine translation, semantic search, and artificial intelligence systems was examined.